Living with the Liminal: Unwieldy Unknowns of Facilitating an Urban Education Cohort of Student Teachers - G. Sue Kasun (Pedagogy & (Im)Possibilities across Education Research, 2017)
The field of education research often overlooks the importance of supervision of the student teaching experience. In this article, I show how as a doctoral student with a focus on education for social justice, I struggled in that role of student teacher supervisor. Despite the students being enrolled in an “urban education” cohort, I felt my positioning was very liminal and perhaps counter-productive to the goal of social justice. I provide reflections and concrete examples of how racism manifested in classrooms and how the student teachers with whom I worked did and did not disrupt it, and how I often was unsure about how to proceed. I also provide implications for educators and researchers.
Keywords: Student Teaching; Pre-Service Teachers; Student Teacher Supervisor; Urban Education; Social Justice